Neonatal hearing screening program and challenges faced by the developing country: a tertiary care hospital experience - Maheen Pyarali; Saeed Akhtar; Maira Adeel; Shabbir Ahmed Mallick; Saher Naseeb Uneeb; Afshan Aslam (Journal of the Pakistan Medical Association, 2023)
Objectives: To screen new-borns to diagnose any hearing impairment early. Method: The prospective, cross-sectional study was conducted at the Department of Otorhinolaryngology, Head and Neck Surgery Liaquat National Hospital, Karachi, from November 1, 2020, to April 30, 2021, and new-borns of either gender aged >12h born via spontaneous vaginal delivery, induced labour, and Caesarean section. A predesigned questionnaire was used to collect detailed case history, including gestational age, duration of labour, and other prenatal, natal, and postnatal risk factors. Otoacoustic emission test was performed, and infants referred twice were scheduled for complete diagnostic evaluation and brainstem evoked response audiometry. Data was analysed using SPSS 23. Results: Of the 267 neonates, 249(93.3%) passed the first screening. Of the remaining 18(6.7%) neonates, 8(44.4%) passed the second screening, while 10(55.5%) were asked to come for a follow-up after three weeks. Of them, 3(30%) returned for check-up, while 7(70%) did not show up. Conclusion: Neonatal risk factors associated with hearing loss need to be identified, and a comprehensive hearing screening programme is required for neonates. Key Words: Hearing, Otoacoustic emission, High risk, Neonatal screening.